Urinary tract infections in Romanian patients with diabetes: prevalence, etiology, and risk factors - Chiţă T; Timar B; Muntean D; Bădițoiu L; Horhat F; Hogea E; Moldovan R; Timar R; Licker M (Dove Medical Press, 2016)
Teodora Chiţă,1,2 Bogdan Timar,1,2 Delia Muntean,1,2 Luminiţa Bădiţoiu,1,3 Florin Horhat,1,2 Elena Hogea,1 Roxana Moldovan,1,3 Romulus Timar,1,2 Monica Licker1,2 1Victor Babes University of Medicine and Pharmacy Timisoara, 2Pius Brinzeu Emergency Hospital, 3Regional Centre of Public Health, Timisoara, Romania Aim: Patients with diabetes mellitus (DM) have an increased risk of infections, especially urinary tract infections (UTIs). The aim of this study was to assess the prevalence and etiology of UTIs and identify the risk factors for their development in patients with DM. Patients and methods: In this retrospective, noninterventional study, the medical records of 2,465 adult patients with DM who were hospitalized in a Diabetes Clinic were reviewed. Data regarding the presence of UTI and possible associated risk factors were collected and their possible relation was analyzed. The study protocol and procedures were approved by the Ethics Committee of Timişoara Emergency Hospital. All data were collected and analyzed using SPSS v.17 statistical software. Results: The prevalence of UTIs in patients with DM was 12.0% (297 cases), being higher in females than in males and higher in patients with type 2 DM compared with patients with type 1 DM. In univariate logistic regression analysis, risk factors associated with UTIs were female gender, age, type 2 DM, longer duration of DM, and the presence of chronic kidney disease and coronary artery disease. Multivariate analysis identified age, duration of DM, and metabolic control (hemoglobin A1c levels) as independent risk factors for UTIs. The gram-negative bacilli from the Enterobacteriaceae family were predominant, with Escherichia coli being the most frequent of them (70.4%). Conclusion: UTIs are a frequent condition associated with DM. It is necessary to improve the care and the screening of UTIs in patients with DM to prevent the occurrence of possible associated severe renal complications. Keywords: urinary tract infections, diabetes mellitus, epidemiology, incidence